The Relationship Between Principal Academic Supervision and School Culture With Teacher Performance at SDN Kabila District, Bolango Regency - Intan Abdul Razak; Besse Marhawati; Warni Tune Sumar (Universitas Negeri Malang, 2023)
Abstract: This study aims to determine: 1) the relationship between the principal's academic supervision and the performance of teachers in SD Negeri Kabila Subdistrict, Bone Bolango Regency, 2) the relationship between school culture and teacher performance in SD Negeri Kabila Subdistrict, Bone Bolango Regency, 3) the relationship between the principal's academic supervision and school culture together with the performance of teachers in SD Negeri Kabila District, Bone Bolango Regency. The method used is quantitative with correlational techniques. The population in this study amounted to 145 teachers. The sampling technique used was random sampling technique. The sample is 59 respondents. Data collection techniques using a questionnaire. Data analysis techniques 1) test the quality of the instrument using the Pearson validity test , Cronbach alpa reliability ; 2) descriptive analysis; 3) normality and linearity test; 4) regression equation analysis; 5) hypothesis testing with partial and simultaneous tests. The results showed: 1) there was a positive and significant relationship between the principal's academic supervision and the performance of teachers in SD Negeri Kabila District, Bone Bolango Regency; 2) there is a positive and significant relationship between school culture and teacher performance in SD Negeri Kabila District, Bone Bolango Regency; 3) there is a jointly positive and significant relationship between the principal's academic supervision and school culture with teacher performance at SD Negeri Kabila District, Bone Bolango Regency. Keywords:Principal Academic Supervision, School Culture, Teacher Performance